Digital repositories and possibilities of their integration into higher education - Vrana, Radovan (Array, 2009)
Abstract – Due to abundance of information available on the Internet, society seeks new types of digital information resources which would facilitate better delivery of information for different purposes. One such information resource type is digital institutional repository. Successful use of digital institutional repositories depends mostly on quality of content they offer, and on unrestricted access to that content. On the other side of the information chain, users i.e. students should be taught how to critically approach and evaluate content they find in digital institutional repositories in order to enrich their learning experience and make it more successful. To find out more about similarities and differences between top 10 largest open access digital information repositories, a comparison of their most important functions was carried out. The results of the comparison give us valuable indicators about possibilities of their use in learning process based on their properties and presence of the most important functions modern information resources should have. Generally speaking, as digital repositories gain more public attention, it can be expected that they will be used even more in future for various purposes, including education.